"I Wouldn't Say We Were Treated Equally": Experiences of Young Adult Stepchildren in the Ghanaian Context. Issue 7 (3rd October 2018) - Hoenayi, Richard K.; Salifu Yendork, Joana
ABSTRACT: Stepparent–stepchild relationships can be difficult to develop and research suggests that the quality of these relationships affects stepfamily functioning and child well-being. This qualitative study explored experiences and perceived determinants of stepchild abuse among 16 youths who are stepchildren on the University of Ghana campus. Positive experiences included receipt of material and emotional support and difficult experiences included favoritism, subjection to severe disciplinary measures, and neglect. Impacts of these experiences were reported. Perceived determinants of stepchild abuse included lack of biological relation, personality of stepparent, financial constrain, stepparent's past experiences, and inheritance. Implications of the findings are discussed.